ANALISIS PENGARUH PERUBAHAN KEMASAN PRODUK TERHADAP PREFENSI PEMBELIAN PADA PT. BAKRIE TELECOM CABANG BOGOR - Yustiana Wardhani; Muhammad Ibrahim (Jurnal Ilmiah Binaniaga, 2008)
Environmental change always occurs continuously in the process of development of a country. This development is directly orindirectly will affect the order of social life, economy, culture, technology and lifestyle community. The changes in the economic, social community of course affect the marketing system in the country. A very rapid technological developments lately has affected all areas of human activity. The development of this technology has tightened competition in the marketing system in the marketing world, where the procedures must innovate continuously in order to win and retain the loyalty of its customers.    Currently in Indonesia there are nine mobile operators include (indosat, Telkomsel, XL, Mobile-8, Three, Flexi, Esia, Smart and Axis). When walking in the center of mobile sales, mobile phones can be seen many types of operators who have their own packaging designs appeal to consumers.    Display a bundle is now realized by the manufacturer is no longer only have the function of protecting and wrapping products but products that increasingly tight competition in the market requires manufactures to think hard in improving the function of packaging to be able to provide attraction to consumers through the artistic aspect, color, graphic, from or the design.    The results of simple correlation analysis found a correlation between changes in the new packaging with the purchase of consumer preferences is 0.293. this suggests that there is a strong relationship between the new packaging Esia with consumer purchasing preferences. While the relationship is positive because it is positive. This means that the new packaging Esia has a strong positive relationship towards the purchase of consumer preferences. This relationship is positive where this Esia packaging changes increase consumer purchasing preferences of Esia.    Analytical results obtained coefficient of determination coefficient of determination between the change in the new packaging with the purchase of consumer preferences is the 0086 (8.6%). This suggests that the level of consumer preferences towards new product packaging can be influenced by the old product by 8.6%, the remaining 91.4%influenced by other factors. The coclusion is that between the old and new packaging packaging there is a correlation effect on customer preferences in choosing which 8.6% can be seen that the old product is still influencing new product, and the remaining 91.4% is another factor affecting.